The Utilization of Internet of Things for Scheduled Monitoring and Automation of Rose Plant Maintenance - Murtaziqoh, Binti; Huda, Miftahul (Universitas Muhammadiyah Sorong, 2025)
An automated monitoring system for scheduled watering and fertilization of rose plants was developed using Internet of Things (IoT) technology to support smart and efficient plant maintenance. The ESP8266 microcontroller serves as the central control unit, integrated with a soil moisture sensor to detect water levels in the growing medium and a Real Time Clock (RTC) module to enable automatic scheduling of fertilization. The system is equipped with an LCD display that shows real-time information on soil moisture, ambient temperature, pump status, and fertilization timing. All data can be monitored remotely in real-time via the Arduino IoT Cloud platform using a smartphone. A buzzer is used as an indicator to provide notification when the fertilization pump is activated or deactivated. The system is designed to assist users with limited time for plant care, ensuring that water and nutrient requirements are consistently maintained. The system was developed using a prototyping approach, followed by functional testing through blackbox testing and User Acceptance Testing (UAT). Results indicate that all main features operate as intended, the user interface is intuitive, and the system demonstrates stable performance. Therefore, this system provides an effective and practical solution for automated, schedule-based rose plant care with remote monitoring capabilities.